Ajustes de coeficientes integrantes de processos físicos e bioquímicos na autedepuração em curso de água de médio porte - Fernandes, Lucianno Eduardo (2016)
The mathematical modeling in the simulation of self-purification capacity in lotic environment is an important tool in the planning and management of hydric resources in hydrographic basin scale. It satisfactorily deals with the self-purification process when the coefficients of physical and biochemical processes are calibrated from monitorated water quality data, which was the main focus of this study. The present study was conducted to simulate the behavior of the parameters OD, BOD5, total phosphorus, E. coli, ammonia, nitrite, nitrate and the total metals cadmium, chromium, copper, lead and zinc in the Uberabinha’s lower course (with an approximate annual growth flow between 4-35 m3/s), in a stretch of 19 km downstream of the treated effluent release by the WWTP of the city. The modelings, on the present study, show the importance of constant water quality parameters monitoration over the water course, based on the comparison of the simulations from calibrated coefficients and coefficients obtained in the literature for the period of June until November 2015. After coefficients calibration, there were good adjustments between simulated and measured data for the parameters OD, BOD, Ptotal, ammonia and nitrate and unsatisfactory adjust for the parameters nitrite and E. coli. About the total metals, the adjustments were not satisfactory on the reservoir’s vicinity of the Small Hydropower Plant Martins, due the considerable increase of the bottom sediment in lentic region. The greatest scientific contribution of this study was to calibrate the decay coefficient K and the quantification of the release by the fund S of total metals in watercourse midsize WWTP pollutant load receptor, justified by the lack of studies in the literature about the subject. For the metals cadmium, chromium, copper, lead and zinc, the borderline for K and S calibrated were: 0.0 to 13.0 day-1 and 0.0 to 1.7 g/m3.day; 0.0 to 0.9 day-1 and 0.0 to 7.3 g/m3.day; 0.0 to 25.0 day-1 and 0.0 to 1.8 g/m3.day; 0.0 to 7.0 day-1 and 0.0 to 40.3 g/m3.day; 0.0 to 30.0 day-1 and 0.0 to 70.1 g/m3.day.